PERTUMBUHAN DAN HASIL JAMUR MERANG AKIBAT PERBEDAAN MEDIA TANAM DAN KONSENTRASI PUPUK SUPER A-1 - Zuyasna Zuyasna; Mariani Nasution; Dewi Fitri (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2011)
The objectives of this study were to investigate several media and liquid organic fertilizer on the growth and the yield of mushroom (Volvariella Volvaceae L) and also to identify the interactions between the two factors. The research was conducted at Lee Guna Gampong Peurada Banda Aceh from 15 June to 23 July 2010. A factorial randomized completely design with three replications was used in this experiment. The first factor evaluated was medium (dried rice stalks, cane bagasse, and cardboard), and the second factor was Super A-1 fertilizer concentrations (0 cc, 7.5, and 15 cc/L). The results showed that media significantly affected stem weight and cap diameter of mushroom. However, the media did not influence primordial initiation, the number of mushrooms, length and diameter of stems. Mushrooms grew best on the medium of cane bagasse. Super A-1 concentration significantly influenced the number of mushrooms, diameter of mushroom cap, and stem diameter, but did not affect mushroom weight. The best concentration of Super A-1 for mushrooms growth was 15cc/L. There were no interactions between the media and concentration Super A-1 based on variables observed in this experiment.